Consumer Purchasing Decisions to Buy Ornamental Plants through E-Commerce in Denpasar City - Wijaya Kusuma I Gusti Agung Bagus; I Gusti Agung Ayu Ambarawati; I Dewa Ayu Sri Yudhari (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
Ornamental plants have an attractive aesthetic value as well as being visually appealing when planted outdoors or indoors. E-commerce has revolutionized consumer purchasing habits, expanding its influence to diverse sectors, such as the ornamental plant industry. This study investigates the type of platform used in the ornamental plant business in Denpasar and examines the influence of convenience, content, response, security, and trust in purchasing decisions for ornamental plants through e-commerce in Denpasar. The results of this study are that convenience and trust have a positive and insignificant effect on purchasing decisions. Content, security, and response have a positive and significant effect on purchasing decisions. response has a significant effect on increasing purchasing decisions for ornamental plants through e-commerce in Denpasar.